Anthropology and civilizational analysis: Eurasian explorations - Jóhann Páll Árnason; Hann, Chris (Suny series, Pangaea II. Global / local studies, 2018)
Introduction : making contact and mapping the terrain / Johann P. Arnason -- Mauss revisited : the birth of civilizational analysis from the spirit of anthropology / Johann P. Arnason -- Approaching civilization from an anthropological perspective : the complexities of Norbert Elias / Hans Peter Hahn -- Civilizational analysis and archaeology : prospects for collaboration / Yulia Prozorova -- The use and abuse of civilization : an assessment from historical anthropology for South Arabia's history / Andre Gingrich -- Civilization as a key guiding idea in South Asia / David N. Gellner -- Indian imbroglios : Bhakti neglected; or, The missed opportunities for a new approach to a comparative analysis of civilizational diversity / Martin Fuchs -- The Indianization and localization of textual imaginaries : Theravada Buddhist statecraft in mainland Southeast Asia and Laos in the context of civilizational analysis / Patrice Ladwig -- Frontier as civilization? : sociocultural dynamics in the uplands of Southeast Asia / Oliver Tappe -- Anthropology, civilizational analysis, and the Malay world / Joel S. Kahn -- Chinese civilization in comparative perspective : some markers / Stephan Feuchtwang -- Technological choices and modern material civilization : reflections on everyday toilet practices in rural South China / Gonçalo Santos -- Theoretical paradigm or methodological heuristic? : reflections on Kulturkreislehre with reference to China / Yang Shengmin and Wu Xiujie -- Nomads and the theory of civilizations / Nikolay N. Kradin -- The "orthodox", "Eurasian", or "Russian orthodox" civilization? / Milena Benovska-Sabkova -- Afterword : anthropology, Eurasia and global history / Chris Hann